Effect of 1-Acetyl-1H-Benzotriazole on Corrosion of Mild Steel in 1M HCl - kamble, P. P.; Dubey, R. S. (Journal of Scientific Research, 2021)
The corrosion inhibition study of 1-acetyl-1H-benzotriazole (ABTZ) on mild steel in 1M HCl solution has been investigated using different techniques like weight loss, open circuit potential (OCP), and potentiodynamic polarization. Results showed that ABTZ inhibited mild steel corrosion in acid solution and indicated that the inhibition efficiencies increased with the increase in inhibitor concentration. The polarization curves revealed that the studied compound behaved as a mixed-type of inhibitor. The adsorption of the inhibitor on the surface of mild steel in the corrosive environment followed the Langmuir isotherm. The presence of thin film formed due to adsorption of ABTZ on mild steel surface is further confirmed by scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDAX).